A REVIEW STUDY ON TRAMADOL ABUSE AMONG EGYPTIAN UNIVERSITY STUDENTS - Phing, Lysher Tan Shu; Aslam, Muhammad Shahzad (Universal Journal of Pharmaceutical Research, 2020)
Tramadol, which is a medication used for moderate and severe pains, has caused drug abuse and addiction to the Egyptian community. This study aimed to observe the prevalence of tramadol abuse among Egyptian university students. By following the PRISMA reporting guideline, a systematic review of evidence was conducted. Search strategy was conducted through PubMed-NCBI to yield appropriate published literature between 2014-2019, as well as performed literature screening, eligibility criteria, and data extraction. The process of selection yielded a total number of 2 studies to be eligible for the review inclusion criteria. The characteristics evaluated that correlate to tramadol were classified into four groups: gender, smoking, alcohol consumption, and failure in exams before. In general, tramadol showed positively associated with other prevalence characteristics. Tramadol is the second most commonly abused drug among university students in Egypt. The review highlights that tramadol abuse has become a common phenomenon among Egyptian university students which necessitates for ample attention. Future research is recommended to identify the causal effects of tramadol abuse and its role as a potential gateway drug. Peer Review History: Received 2 December 2019; Revised 10 January 2020; Accepted 26 February; Available online 15 March 2020 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewer(s) detail: Hebatallaha A Moustafa , Ain Shams University, Egypt, anasweety2003@yahoo.com Prof. Dr. Hassan A.H. Al-Shamahy , Sana'a University, Yemen, shmahe@yemen.net.ye Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com